Improving the Efficiency of Supply Chain in Agricultural Produce Using Blockchain - Anjan, Spurthi N; Sequeira, Johnson P (International Journal of Computer Sciences and Engineering, 2025)
The asymmetry in the information pertaining to agricultural supply chain is extremely evident in developing countries like India. Also, the entity worst affected by this asymmetry are the farmers, who do not receive their fair share of in spite of being the most crucial contributors to this food cycle. Moreover, dealing with specific agricultural produce which h ave a short shelf life becomes a complex task with higher rate of wastage every year. With the help of a distributed ledger system in place, we help track the agricultural produce supply chain in every part of the country by replacing whatever supply chain tracking or centralized record keeping mechanism is already in place to provide complete transparency of the lifecycle of produce and enabling faster transactions between nodes and in turn helping the farmers reap the best benefits of their hard work. This would bring complete transparency in nodes where the efficiency is lost, parti cularly, brokers, distributors, regulators, retailers, government departments, etc., Easy and accurate access to this information will improve the overall efficiency of the supply chain and in turn benefit all the entities involved equally.